A New Multilevel Inverter Structure For High-Power Applications using Multi-carrier PWM Switching Strategy - Rasoul Shalchi Alishah; Seyyed Hossein Hosseini (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In recent, several numbers of multilevel inverter structures have been introduced that the numbers of circuit devices have been reduced.  This paper introduces a new structure for multilevel inverter which can be used in high-power applications. The proposed topology is based on cascaded connection of basic units. This topology consists of minimum number of circuit components such as IGBT, gate driver circuit and antiparallel diode. For proposed topology, two methods are presented for determination of dc voltage sources values. Multi-carrier PWM method for 25-level proposed topology is used. Verification of the analytical results is done using MATLAB simulation.